Emerging treatments in management of prostate cancer: biomarker validation and endpoints for immunotherapy clinical trial design - Slovin, Susan F (Immunotargets Ther, 2013)
The rapidly emerging field of immunotherapy and the development of novel immunologic agents that have been approved in melanoma and successfully studied in lung cancer, kidney cancer, and prostate cancer have mandated that there be uniformity in clinical trial analysis beyond conventional survival endpoints and imaging. This includes some measure of determining whether the immunologic target is hit and how the treatment has impacted on the immune system in toto. While melanoma is leading the field towards these ends, there is some doubt that not all of the recent successes with immune therapies, for example, checkpoint inhibitors, will be effective for every cancer, and that the toxicities may also be different depending on the malignancy. This review serves to elucidate the current issues facing clinical investigators who perform immunologic trials targeted at patients with prostate cancer and discusses the challenges in assessing the right immunologic endpoints to demonstrate biologic/immunologic targeting leading to clinical benefit.